Temperature-related Mortality in Belgrade in the Period 1888–2008 - S. Djurdjev, Branislav; Arsenović, Daniela; Savić, Stevan (Acta geographica Slovenica, 2012)
The paper uses air temperature and crude death rate data from Belgrade in the period from 1888 to 2008, in order to show expected correlation. Basic statistical analysis demonstrates statistically significant correlation values between these parameters. The starting assumption was that people in earlier times were more sensitive to extreme cold temperatures, particularly in the winter season. Statistical results confirm previous mentioned assumptionparticularly in the period before the First World War.Further analysis showed that in the last twenty years, air temperatures and death rates have opposite correlation outcomes. Statistical analysis points out that, in the last twenty years, death rates are increasing more rapidly in the summer season, due to increasing frequencies of extreme air temperature events.